Observation of scissors modes in solid state systems with a SQUID. (19th February 2016) - Hatada, Keisuke; Hayakawa, Kuniko; Palumbo, Fabrizio; Marcelli, Augusto
Abstract : Collective oscillations of deformed ions, called scissors modes, in their unit cells were predicted some time ago. Here it is proposed to detect them by measuring using a SQUID the associated variation of the magnetic field. Abstract : The occurrence of scissors modes in crystals that have deformed ions in their unit cells was predicted some time ago. The theoretical value of their energy is rather uncertain, however, ranging between ten and a few tens of eV, with the corresponding widths of 10 −7 to 10 −6 eV. Their observation by resonance fluorescence experiments therefore requires a photon spectrometer covering a wide energy range with a very high resolving power. Here, a new experiment is proposed and discussed in which such difficulties are overcome by measuring with a superconducting quantum interference device (SQUID) the variation of the magnetic field associated with the excitation of scissors modes.